The Many Faces of Christ: Responding to Suffering and Transcendence in the Thought of Barth and Moltmann - Sugiri, Widjaja (LPPM - Sekolah Tinggi Teologi Indonesia Jakarta, 2024)
This article discusses the theological thoughts of Karl Barth and Jürgen Moltmann on Christ, with a focus on the implications of their understandings for the church and society today. The background of this research is rooted in the development of Reformed theology, which places Christ at the center, as well as the challenges of the modern world. The aim of this study is to analyze the contributions of Barth and Moltmann in addressing contemporary social issues through Christology. The methodology used is a literature review with a qualitative approach, involving an analysis of the major works of both theologians, as well as relevant literature. The findings reveal that Barth emphasizes Christ as the transcendent revelation of God, while Moltmann highlights God’s solidarity with human suffering, particularly in a social context. Both theologians provide important insights for the church in addressing social issues, urging the church to not only focus on personal salvation but also to actively engage in creating justice and peace. The contribution of this research is to offer a new understanding of the role of the church and Christians in addressing social challenges through the teachings of Christ. Artikel ini membahas pemikiran teologis Karl Barth dan Jürgen Moltmann mengenai Kristus, dengan fokus pada implikasi pemahaman mereka terhadap gereja dan masyarakat masa kini. Latar belakang penelitian ini berakar pada perkembangan teologi Reformed yang menempatkan Kristus sebagai pusat teologi, serta tantangan dunia modern yang semakin kompleks. Tujuan penelitian ini adalah untuk menganalisis kontribusi pemikiran Barth dan Moltmann dalam menjawab isu-isu sosial kontemporer melalui teologi Kristus. Metode yang digunakan adalah kajian pustaka dengan pendekatan kualitatif, yang melibatkan analisis terhadap karya-karya utama kedua tokoh tersebut, serta kajian literatur terkait. Hasil penelitian menunjukkan bahwa Barth berfokus pada Kristus sebagai wahyu Tuhan yang transenden, sementara Moltmann menekankan solidaritas Tuhan dengan penderitaan umat manusia, khususnya dalam konteks sosial. Kedua teolog ini memberikan wawasan penting bagi gereja dalam menghadapai masalah sosial, dengan mengajak gereja untuk tidak hanya memikirkan keselamatan pribadi, tetapi juga berperan aktif dalam menciptakan keadilan dan kedamaian. Kontribusi penelitian ini adalah memberikan pemahaman baru mengenai peran gereja dan umat Kristen dalam menghadapi tantangan sosial melalui ajaran Kristus.